Moda democrática: o jeans e seus processos comunicativos - Lima, Ana Patrícia Batista de (2009)
This research has the purpose to investigate the jeans pathway along the years binding it to democratic aspect, as a garment adopted for different social groups. Here is analyzed how and why the jeans fashion is a deep-rooted custom in social context and what is the role of Advertising on the construction of this garment´s image. Knowing that fashion is defined from social levels, this study analyzes the hypotheses that this garment followed the inverse pathway of fashion, before democratizing in all social classes. From a garment made for miners and hard workers in the beginning of it´s trajectory, changing into luxury object. Despite, even being this upgrade on the social stratum, we realize that, until today, this garment is present in all of them. In order to find out cultural and social values that belongs to jeans, the advertising communication is present, to fulfill an important role as it represents an appeal tool for consumption, that indicates values, tastes and ideologies from each decade, principally when it talks about fashion. In the sense of capturing social perception about jeans, were applied questionnaires to individuals borned from 50´s to 90´s decade. In the analysis, data are crossed with the possible advertising messages from the ad pieces analyzed and the image that the individual have on his own mind about this garment. The main analysis methodology of the collected data, being them the answers captured from questionnaires or from magazines advertise materials, was the Peirce´s essence search for phenomenon distancing, when we observe it and let it talk and answer what it is. In the sense of permit the action of the object, and through of induction and deduction, extract analysis, by the characteristics that repeat or vanish, being laws, habits or changing them. The present work is based in some author´s thoughts. For the history of fashion, we have the Crane and Roche´s historic reports and the value contribution of the sociologist Simmel. The jeans history is explained by Sullivan and Huiguang and Lv, and is present along the research. In the discussion about the principles of advertising, marketing and fashion we can appreciate the authors Lipovestky (the fast and a concrete fashion), Bauman (consumers society), Baudrillard (consumption society), Martins (brand value), Predebon (brand identity), Kotler (classic marketing principles) and Iasbeck (contemporaneous speech of advertising). To categorization of the analysis changeable from the ad pieces, it was used the principles of the space organization like mediation proposed by Ferrara and the index of visual language, proposed by Dondis